Problem music and self-harming - North, Adrian; Hargreaves, David (John Wiley & Sons, Inc., 2006)
Academics and protest groups have claimed that “problem music” (hard rock, hip hop/rap, & punk) causes self-injurious thoughts/behaviors among fans. In this study we investigated whether the relationship is mediated by self-esteem, delinquency, and conservatism; and whether first exposure to problem music preceded self-injurious thoughts. A liking for problem music was associated with fourof the five self-injurious measures, although these significant relationships were weakened (into nonsignificance in the case of two self-injurious measures) when the mediating variables were included. Listening to problem music did not precede self-injurious thoughts. Problem music is associated with self-injurious thoughts and behaviors, but this relationship is mediated by other factors and the former does not seem to cause the latter.